2018
DOI: 10.1039/c7sc04687a
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the redox non-innocence of a phenalenyl ligand toward efficient nickel-assisted catalytic hydrosilylation

Abstract: The hydrosilylation of olefins by a nickel(ii) catalyst assisted by a redox non-innocent phenalenyl (PLY) ligand is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 66 publications
8
55
0
Order By: Relevance
“…The successful catalytic reduction of carboxylic acid, which is greatly supported by the redox active delocalized ligand backbone, inspired us to study the mechanistic course of the reaction thoroughly. Our previous finding that the PLY backbone behaves as a redox reservoir and triggers a radical catalyzed reaction, prompted us to examine whether this reduction also adopts a radical pathway 43. In agreement with this hypothesis, we observed that the addition of a radical quencher TEMPO in two equivalents completely shuts down the reaction.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The successful catalytic reduction of carboxylic acid, which is greatly supported by the redox active delocalized ligand backbone, inspired us to study the mechanistic course of the reaction thoroughly. Our previous finding that the PLY backbone behaves as a redox reservoir and triggers a radical catalyzed reaction, prompted us to examine whether this reduction also adopts a radical pathway 43. In agreement with this hypothesis, we observed that the addition of a radical quencher TEMPO in two equivalents completely shuts down the reaction.…”
Section: Resultssupporting
confidence: 76%
“…2b). The close proximity of these reduction potential values to those of previously reported (PLY-O,O) 2 Ni(THF) 2 strongly suggests the reductions are primarily ligand based 43. The Δ E 2–1 value from the voltammogram is –0.24 V, which is also in close agreement to bis-phenalenyl–boron complexes bearing the same phenalenyl based ligand (the Δ E 2–1 values are –0.29 and –0.28 V).…”
Section: Resultssupporting
confidence: 76%
“…It may be noted that the same NBMO of phenalenyl based molecules earlier played a key role in designing molecules with several intriguing properties such as organic magnets, conductors, organic spin based electronics, and batteries . Only recently, the use of phenalenyl‐based molecules has been evolving for the design of various catalysts . The topic of phenalenyl‐based molecules to design various catalysts and spin electronic materials was reviewed recently …”
Section: Methodsmentioning
confidence: 99%
“…[25][26][27][28][29][30][31][32][33][34] Only recently,t he use of phenalenyl-based molecules has been evolving for the design of variousc atalysts. [35][36][37] The topico fp henalenyl-based moleculest od esign variousc atalysts ands pin electronic materials was reviewed recently. [38] We initiatedt he present study by optimizing the reaction conditions for direct CÀHa rylation of thiophene( 2a)w ith para-chlorophenyl diazo-tetrafluoroborate salt (3a)u sing Fe(PLY-O,O) 3 (1)c atalyst (see the Supporting Information, Ta ble S1).…”
Section: Dedicatedtoprofessor Dietmar Stalke On the Occasion Of His 6mentioning
confidence: 99%
“…20 Recently, such in situ generated mono-reduced phenalenyl based radicals were reported in designing cathode materials for single component H 2 O 2 fuel cell 21 and in electron transfer catalysis during various organic transformations. [22][23][24][25] Such approach using in-situ generated mono-reduced phenalenyl radicals opens a possibility to bridge between two seemingly dissimilar areas such as spin-electronics and catalysis. 26…”
Section: Introductionmentioning
confidence: 99%